268 Administering an appeasing substance to optimize welfare and performance of receiving cattle. (30th November 2020) - Colombo, Eduardo; Cooke, Reinaldo F; Brandão, Alice; Wiegand, Jacob; Schubach, Kelsey; Sowers, CiCi A; Duff, Glenn; Gouvea, Vinicius N; Cappellozza, Bruno I
Abstract: This experiment evaluated the impacts of bovine appeasing substance (BAS) administration on performance, health, and physiological responses of feedlot cattle during a 45-d receiving period. A total of 342 recently-weaned Angus-influenced steers, originating from 16 cow-calf operations, were obtained from an auction yard on d -1 and road-transported (12 h) to the feedlot. Upon arrival on d 0, body weight (BW) was recorded and steers were ranked by BW and source and assigned to receive BAS (Nutricorp, Araras, SP, Brazil; n = 171) or placebo (diethylene glycol monoethyl ether; CON; n = 171). Treatments (5 mL) were topically applied to the nuchal skin area of each animal. Within treatment, calves were allocated to 1 of 24 drylot pens (12 pens/treatment) and received a free choice total-mixed ration from d 1 to 45. Calves were assessed for bovine respiratory disease (BRD) signs and feed intake was recorded from each pen daily. Steer BW was again recorded on d 1, 7, 17, 31, and 45, whereas blood samples were collected from 5 steers/pen concurrently with each BW assessment. Average daily gain was greater (P = 0.05) in BAS vs. CON calves, although final BW did not differ (P = 0.36) between treatments. No treatment effects were detected for feed intake (P = 0.95), resulting in greater (P = 0.05) feed efficiency in BAS vs. CON steers. No treatment effects were detected (P ≥ 0.37) for plasma concentrations of haptoglobin, whereas plasma cortisol concentrations were greater (P = 0.05) in CON vs. BAS steers on d 7 (treatment × day; P = 0.07). Incidence of BRD was greater (P ≤ 0.05) in BAS vs. CON on d 6 to 10 and d 18 to 21 (treatment × day; P < 0.01), although overall BRD incidence did not differ (P = 0.24) between treatments. The number of antimicrobial treatments required per steer diagnosed with BRD symptoms to recover from sickness was greater (P = 0.04) in CON vs. BAS calves. No treatment differences were detected (P ≥ 0.41) for mortality incidence, or proportion of steers removed from the experiment due to extreme sickness. Results from this experiment indicate BAS administration upon feedlot entry improved average daily gain by enhancing feed efficiency. Administration of BAS facilitated earlier detection of BRD and reduced the need for antimicrobial treatments. Collectively, these results suggest BAS administration as a promising strategy to benefit performance and immunocompetence of feedlot receiving cattle.